Gross Description and Osteometrics of the Axial Skeleton (Ribs and Vertebrae) of Eidolon Helvum (African Fruit Bat) (Nigerian Journal of Physiological Sciences, 2021)
anatomical peculiarities, gross description and morphometrics of the ribs. Fifteen adult bats were used for this study. The vertebral formula was C7T13-14L3-4S7Cd3-4. Spinous process was rudimentary on thoracic vertebrae 1 to 7. The numbers of the ribs ranged from 13 to 14, with the longest being rib 7, and the shortest being rib 14. Twenty percent of the males and 50% of the females had 14 ribs; the male and one female had the 14th rib being unilateral (present on the right side of male and left side of female). The first rib did not articulate directly with the sternum, but through a connecting triangular-shaped bone. The thoracic inlet and outlet were larger in males, relative to the females (inlet height – males 21.82 ± 2.68 mm, females 20.44 ± 4.91 mm; outlet height – males 36.46 ± 3.76 mm, females 33.23 ± 4.33 mm). The sternum was segmented, five in number and had a ventral elongation like the avian keel. Data obtained may find application in comparative and applied anatomy, and forensic medicine.
Keywords: Eidolon helvum; Axial skeleton; Osteology; Osteometrics; Triangular bone